2015
DOI: 10.1111/lam.12435
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic changes contributing to Enterobacter gergoviae biocide resistance

Abstract: Recurrent contaminations of cosmetics products by Ent. gergoviae, needed a better understanding concerning the bacterial adaptation to preservative agents, with particular concern to triclosan and MIT-CMIT. We demonstrated that bacteria response is associated to various mechanisms represented by expression of external appendages (pili or fimbriae) that control cell motility and biofilm formation and evolving as the concentration of biocides adaptation increased. Such mechanisms which are not chemical specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Recently, however, ESBL type SHV and carbapenemase type (IMP or KPC) producers were described in this species (113). With regard to biocides, due to membrane modifications, esterase production, and the modulation of enzymes involved in oxidative detoxification, this species has a natural resistance to the parabens, triclosan, and methylisothiazolinonechloromethylisothiazolinone (MIT-CMIT), which are preservatives used in this type of product (114,115). Such results explain the ability of this species to contaminate cosmetics from a source probably of unknown plant origin (116,117).…”
Section: Enterobacter Gergoviaementioning
confidence: 99%
“…Recently, however, ESBL type SHV and carbapenemase type (IMP or KPC) producers were described in this species (113). With regard to biocides, due to membrane modifications, esterase production, and the modulation of enzymes involved in oxidative detoxification, this species has a natural resistance to the parabens, triclosan, and methylisothiazolinonechloromethylisothiazolinone (MIT-CMIT), which are preservatives used in this type of product (114,115). Such results explain the ability of this species to contaminate cosmetics from a source probably of unknown plant origin (116,117).…”
Section: Enterobacter Gergoviaementioning
confidence: 99%
“…On the other hand, the biofilms formation could also contribute to the resistance of these species. Indeed, Périamé et al (2015) indicate that biofilm production mediates the adaptation of P. gergoviae to MIT-CMIT. The role of biofilm formation in the resistance of P. aeruginosa to biocides has also been described (El-Banna et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It added five parabens to the list of substances prohibited in cosmetics. Moreover, bacterial species such as P. gergoviae were shown to have innate resistance properties to parabens (Valkova et al, 2002) and the ability to acquire resistance to other preservatives such as triclosan, methylisothiazolinone and chloromethylisothiazolinone (MIT‐CMIT; Périamé et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we showed that industrial Pseudomonas aeruginosa strains uniquely possess large segments of DNA known as megaplasmids, which confer extra genomic capacity with Ն500 genes and thus may play a role in preservative resistance (3). Furthermore, studies with Pluralibacter strains and other Gram-negative bacteria have shown that there are clear links between preservative resistance and outer membrane modifications (4,5). The genetic changes underpinning these mechanisms of resistance are not well understood but may be elucidated with advances in genomics (6).…”
mentioning
confidence: 99%